Disrupting reconsolidation by PKA inhibitor in BLA reduces heroin-seeking behavior - Zhang, Yanghui; Li, Haoxian; Hu, Ting; Zhao, Zijin; Liu, Qing; Li, Haoyu (Frontiers in Cellular Neuroscience, 2022)
Drug abuse is considered a maladaptive pathology of emotional memory mediating craving and relapse induced by drug-associated stimuli or drugs. Pharmacological or behavior treatment that disrupts reconsolidation can effectively attenuates drug-seeking in animal models or addicts. Reconsolidation is an independent process with a specific time window followed by the reactivation of drug-associated stimulus depending on the basolateral amygdala (BLA). We hypothesized that heroin-memory reconsolidation requires cAMP-dependent protein kinase A (PKA) of BLA based on the fundamental effect of PKA in synaptic plasticity and memory process. After ten days of acquisition, rats underwent eleven days of extinction training and then received the intra-BLA infusions of the PKA inhibitor Rp-cAMPS at different time points with/without a reactivation session. The results show that PKA inhibitor treatment in the reconsolidation time window disrupts the reconsolidation and consequently reduces cue-induced reinstatement that is resistant to heroin-priming and spontaneous recovery of heroin-seeking behavior in rats. By contrast, in intra-BLA infusion of PKA inhibitor 6h after reactivation or without reactivation has no effect on cue-inducement reinstatement. These data suggest that PKA inhibition in the BLA disrupts reconsolidation of heroin-associated memory, reduces subsequent drug seeking and prevents relapse, which is retrieval-dependent and time-limited.